2010
DOI: 10.1007/s00520-010-0859-0
|View full text |Cite
|
Sign up to set email alerts
|

Are nurses and physicians able to assess which strategies adolescents recently diagnosed with cancer use to cope with disease- and treatment-related distress?

Abstract: Health-care staff's possibilities to assess how patients cope with disease- and treatment-related distress should be increased. A number of changes in education and the organization of clinical care, especially with regard to assessing patients' needs, are suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…The continued distress experienced by a subset of the present sample and the moderate agreement between parent and adolescents supports this recommendation. Additionally, a recent study indicated that nurses, one of the primary conduits of referrals for patients and families, may overestimate adolescents' ability to manage distress (Engvall et al, 2011). This finding suggests that adolescents who are experiencing significant distress may not be identified by their healthcare provider, even those with close contact, due to overestimations of emotional competence.…”
Section: Discussionmentioning
confidence: 99%
“…The continued distress experienced by a subset of the present sample and the moderate agreement between parent and adolescents supports this recommendation. Additionally, a recent study indicated that nurses, one of the primary conduits of referrals for patients and families, may overestimate adolescents' ability to manage distress (Engvall et al, 2011). This finding suggests that adolescents who are experiencing significant distress may not be identified by their healthcare provider, even those with close contact, due to overestimations of emotional competence.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the measures used were not designed for or validated on YA samples, a limitation characteristic of all psychosocial research in YA oncology at this time. [4] The sample for this study was restricted to YAs with advanced disease[38] and included a broad age range that captures multiple developmental transitions. Examination of coping across disease trajectory and developmental phases within young adulthood may be important.…”
Section: 0 Discussionmentioning
confidence: 99%
“…Coping strategies employed whilst experiencing side effects during treatments have been an important oncology nursing research focus. Caution need to be taken when intervening as they may be ineffective and potentially harmful (Engvall et al, 2011). Psychological distress encompasses a series of negative emotions such as anxiety and depression, which are the end states of a maladaptive process (Zabalegui et al, 2005;Zainal et al, 2007;Saniah and Zainal, 2010).…”
Section: Symptom Experiences and Coping Strategies Among Multiethnic Solid Tumor Patients Undergoing Chemotherapy In Malaysiamentioning
confidence: 99%